Fracture toughness and fatigue crack growth rate properties in wire + arc additive manufactured Ti-6Al-4V - Zhang, Xiang; Martina, Filomeno; Ding, Jialuo; Wang, X.; Williams, Stewart W. (Wiley, 2016)
This paper presents an experimental investigation of the fracture and fatigue crack growth properties of Ti-6Al-4V produced by the Wire + Arc Additive Manufacture (WAAM) process. First, fracture toughness was measured for two different orientations with respect to the build direction; the effect of wire oxygen content and build strategy were also evaluated in the light of microstructure examination. Second, fatigue crack growth rates were measured for fully additive manufactured samples, as well as for samples containing an interface between WAAM and wrought materials. The latter category covers five different scenarios of crack location and orientation with respect to the interface. Fatigue crack growth rates are compared with that of the wrought or WAAM alone conditions. Crack growth trajectory of these tests is discussed in relation to the microstructure characteristics
Keywords: wire + arc additive manufacture; titanium; fracture toughness; fatigue crack growth; microstructure